2010
DOI: 10.1111/j.1365-2486.2009.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

The European carbon balance. Part 1: fossil fuel emissions

Abstract: We analyzed the magnitude, the trends and the uncertainties of fossil-fuel CO2 emissions in the European Union 25 member states (hereafter EU-25), based on emission inventories from energy-use statistics. The stability of emissions during the past decade at EU-25 scale masks decreasing trends in some regions, offset by increasing trends elsewhere. In the recent 4 years, the new Eastern EU-25 member states have experienced an increase in emissions, reversing after a decade-long decreasing trend. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 29 publications
(28 reference statements)
0
69
0
Order By: Relevance
“…Marland et al (1999) pursued a systematic comparison of the CDIAC and EDGAR data sets and Marland et al (2007) reported a systematic comparison of estimates from CDIAC, EIA, and UNFCCC for the three countries of North America. Macknick (2009) has recently attempted a systematic comparison of four emissions data sets, and Ciais et al (2010) have done a similar comparison for the countries of the European Union. A conclusion from these comparisons is that despite apparent similarity, there are differences in assumptions and boundary conditions that make it difficult to do quick quantitative comparisons.…”
Section: Different Global Data Sets Availablementioning
confidence: 99%
See 2 more Smart Citations
“…Marland et al (1999) pursued a systematic comparison of the CDIAC and EDGAR data sets and Marland et al (2007) reported a systematic comparison of estimates from CDIAC, EIA, and UNFCCC for the three countries of North America. Macknick (2009) has recently attempted a systematic comparison of four emissions data sets, and Ciais et al (2010) have done a similar comparison for the countries of the European Union. A conclusion from these comparisons is that despite apparent similarity, there are differences in assumptions and boundary conditions that make it difficult to do quick quantitative comparisons.…”
Section: Different Global Data Sets Availablementioning
confidence: 99%
“…Ciais et al (2010) compared two different emission maps over Europe. An increasing difference between the two products was obtained down to finer spatial and temporal scales, with root mean square error between the maps increasing to 40 g C m −2 d −1 at 50 km resolution, and being higher in winter than in summer.…”
Section: Uncertainties Associated With the Ffco2 Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These inventories are based upon activity data and corresponding emission factors and uncertainties can be substantial, particularly at the city scale. Ciais et al (2010a) showed uncertainties of 19 % of the mean emissions at country scale in the 25 EU member states and up to 60 % at scales less than 200 km. Currently there is no legal obligation for individual cities to report their emissions; however, as environmental awareness increases and actions are taken to reduce urban GHG emissions, monitoring of city emissions to evaluate the success of emissions reduction schemes becomes an important consideration.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts to compare various FFCO 2 estimates (e.g. Marland et al, 2007;Macknick, 2009;Afsah and Aller, 2010;Ciais et al, 2010;Andres et al, 2012), but the task is not trivial. Francey et al (2013) suggest large underreporting, and hence uncertainty, in the global total of FFCO 2 emissions around years 1995Á2005 based on atmospheric measurements.…”
Section: Introductionmentioning
confidence: 99%